2013
DOI: 10.2174/0929867311320030014
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drug Effects in Schizophrenia: A Review of Longitudinal fMRI Investigations and Neural Interpretations

Abstract: The evidence that antipsychotics improve brain function and reduce symptoms in schizophrenia is unmistakable, but how antipsychotics change brain function is poorly understood, especially within neuronal systems. In this review, we investigated the hypothesized normalization of the functional magnetic resonance imaging (fMRI) blood oxygen level dependent signal in the context of antipsychotic treatment. First, we conducted a systematic PubMed search to identify eight fMRI investigations that met the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 105 publications
(111 reference statements)
3
30
0
Order By: Relevance
“…41 This result corresponds to conclusions from a recent review that the BOLD signal in speci c neural regions normalizes over the course of antipsychotic treatment 42 and to a recent resting-state fMRI study showing that antipsychotic-induced improvement of psychotic symptoms was accompanied by increased functional connectivity among striatal regions, the ACC and the anterior insula. 12 The antipsychotic effect in treated patients can perhaps be explained by the underlying structure as well, given that insular and ACC volumes increase with increasing antipsychotic exposure in psychotic patients.…”
Section: J Psychiatry Neurosci 2016;41(6)supporting
confidence: 86%
“…41 This result corresponds to conclusions from a recent review that the BOLD signal in speci c neural regions normalizes over the course of antipsychotic treatment 42 and to a recent resting-state fMRI study showing that antipsychotic-induced improvement of psychotic symptoms was accompanied by increased functional connectivity among striatal regions, the ACC and the anterior insula. 12 The antipsychotic effect in treated patients can perhaps be explained by the underlying structure as well, given that insular and ACC volumes increase with increasing antipsychotic exposure in psychotic patients.…”
Section: J Psychiatry Neurosci 2016;41(6)supporting
confidence: 86%
“…First, effects of medications were not ruled out. Antipsychotic drug effects in schizophrenia may include global brain functions and connectivity (Abbott, Jaramillo, Wilcox, & Hamilton, 2013; Kraguljac et al., 2015). In particular, antipsychotics could alter neural activity and functional connectivity of the amygdala (Rasetti et al., 2009) and different antipsychotics could have different effects on amygdala activity during emotional processing (Surguladze et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…18 A recent review of differential effects of antipsychotic medication concluded that lower dopaminergic receptor affinity and moderate to high serotonergic affinity is associated with greater activation of the prefrontal cortex. However, unexpectedly, clozapine appeared to cause a decrease in prefrontal activation in most studies.…”
Section: Differential Sga Effects On Brain Activationmentioning
confidence: 99%
“…17 In fact, an increasing number of studies have documented the effects of SGA treatment on neural functions. 18 These studies mostly focused on the recovery of altered frontocortical activation patterns, showing normalization of the blood oxygen level-dependent (BOLD) signal with antipsychotic treatment. 18 To elucidate differential effects of pharmacologic profiles, imaging investigations directly comparing different antipsychotic agents are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation